(untitled) (Damascus University Journal for legal sciences, 2025)
Despite the many legal guarantees devoted to local units in order to perform the tasks entrusted to them and their relative independence, it is impossible for them to carry out their tasks and functions in the absence of an institutional structure, foremost of which is the executive bodies. Among the criteria that are taken into account to measure the extent of the independence of local units, and their enjoyment of real powers in the administrative system of the state, is the size of the functions performed by local units compared to those carried out by the central authority and its branches, thus the association of executive bodies with local units has become an institutional fact that should not be ignored ,and Setting criteria that will activate the link in the best way. This research dealt with the study and scrutiny of the idea of ​​the link between the local units and the executive bodies in all its aspects, and reached the importance of the local units enjoying legal powers over the executive bodies in line with the objectives of the local administration law.